Pengaruh Suhu Waktu Pengecoran Terhadap Kuat Tekan dan Tarik Beton - Nita Bonita Rombe; Junus Mara; Desi Sandy (Paulus Civil Engineering Journal, 2020)
This study discusses how much influence the temperature of the casting time has on the compressive strength and tensile strength of concrete. The purpose of this study was to determine how much influence the temperature of the casting time has on the optimal compressive strength and tensile strength of concrete. The test specimen for normal concrete mixtures with a compressive strength plan of f'c = 30 Mpa, using a cylinder with a diameter of 15 cm and a height of 30 cm was 36 pieces. The casting of test objects is carried out with variations in time temperature in the morning, afternoon, evening, and night. The test results show that the maximum compressive strength and split tensile strength of concrete are 31.31 MPa and 2.64 MPa at 23 ° C in the morning. The temperature of the casting time does not significantly affect the compressive and tensile strength of the resulting concrete.